(untitled) - DONISIA YOSOA, HELENA (LATERNE, 2016)
The four components of language skills, are listening, speaking, reading and writing. Talk is a form of speech acts as the noise produced by the vocal organs accompanied by gestures and facial lineament produced. In accordance with its function to speak, is the medium used by humans to communicate. A media adequately put into practice in teaching and learning is a word card game. The game is included in the flash memory card. In this case, the card media storage words together on the subject. Learning topics stringing and words that speak in the pun media card in the first idea to support. the formulation of the problem in this research is how the application of the card in speaking skills and the ability to speak conversational abilities of students of Class X SMAN 1 MIA 1 Gedangan Sidoarjo using the word card media. The aim of this research is to talk about the word card game media use of the German language skills class X MIA 1 SMA Negeri 1 Gedangan Sidoarjo in learning. this study is a qualitative study with observation sheets, questionnaires and documentation as a research tool. Observation sheet used to determine the activities of students, spoken by a media card and the words student activity using the word card media occurs during the learning process, while the questionnaire was used to assess the response and the motivation of the students after using the word card media in the learning activities German language skills. The results of this study show that the card game media received a good response from the students about the activities of the German Sprachkenntnissein class. With the map media said, the students are motivated to learn and participate during the teaching and learning take place. media card Students working with these words in teams to help each other in learning and learning fun situation. Your ability to speak does use given by a media card word. Media shows the card game can be used as an alternative for German teachers as a teaching tool in teaching and learning, especially students actively help in the learning process and students can talk to improve skills.